Isolation and description of Selenomonas timonae sp. nov., a novel Selenomonas species detected in a gingivitis patient. Issue 10 (6th October 2021) - Antezack, Angéline; Boxberger, Manon; Ben Khedher, Mariem; La Scola, Bernard; Monnet-Corti, Virginie
Abstract : A Gram-stain-negative bacterium, designated strain Marseille-Q3039 T, was isolated from subgingival dental plaque of a woman with gingivitis in Marseille, France. Strain Marseille-Q3039 T was found to be an anaerobic, motile and spore-forming crescent-shaped bacterium that grew at 25–41.5 °C (optimum, 37 °C), pH 5.5–8.5 (optimum, pH 7.5) and salinity of 5.0 g l −1 NaCl. The results of 16S rRNA gene sequence analysis revealed that strain Marseille-Q3039 T was closely related to Selenomonas infelix ATCC 43532 T (98.42 % similarity), Selenomonas dianae ATCC 43527 T (97.25 %) and Centipedia periodontii DSM 2778 T (97.19 %). The orthologous average nucleotide identity and digital DNA–DNA hybridization relatedness between strain Q3039 T and its closest phylogenetic neighbours were respectively 84.57 and 28.2 % for S. infelix ATCC 43532 T and 83.93 and 27.2 % for C. periodontii DSM 2778 T . The major fatty acids were identified as C13 : 0 (27.7 %), C15 : 0 (24.4 %) and specific C13 : 0 3-OH (12.3 %). Genome sequencing revealed a genome size of 2 351 779 bp and a G+C content of 57.2 mol%. On the basis of the results from phenotypic, chemotaxonomic, genomic and phylogenetic analyses and data, we concluded that strain Marseille-Q3039 T represents a novel species of the genus Selenomonas, for which the name Selenomonas timonae sp. nov. is proposed (=CSUR Q3039=CECT 30128).